2016
DOI: 10.1002/dta.2108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fibronectin 1 in one dried blood spot and in urine after rhGH treatment

Abstract: Since the appearance of recombinant human growth hormone (rhGH) in the 1980s, its expansion and acquisition through the black market has increased, so the detection of its abuse continues to be a challenge. New biomarkers that are more reliable and sensitive, allowing a larger detection window, are still needed. In this line, Fibronectin 1 (FN1) has been proposed as a potential genetic and protein biomarker of rhGH abuse in peripheral blood lymphocytes, serum, and plasma. However, logistic problems associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Other studies have seen that GH-2000 score is a good marker to detect higher doses of recGH, [11][12][13] whereas with lower doses used here, the GH-2000 score seems not to be valid. 19,20 Another putative approach may be to longitudinally also monitor the different GH isoforms, since the isoform ratio appears to be quite stable in each participant. In fact, dur- This highlights the importance of monitoring not only GH-dependent pathways but also markers of bone and collagen turnover.…”
Section: Hours and 3 Hours) After An Injection This Results Is In Agrmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have seen that GH-2000 score is a good marker to detect higher doses of recGH, [11][12][13] whereas with lower doses used here, the GH-2000 score seems not to be valid. 19,20 Another putative approach may be to longitudinally also monitor the different GH isoforms, since the isoform ratio appears to be quite stable in each participant. In fact, dur- This highlights the importance of monitoring not only GH-dependent pathways but also markers of bone and collagen turnover.…”
Section: Hours and 3 Hours) After An Injection This Results Is In Agrmentioning
confidence: 99%
“…There are several proteins that have been identified in relation to GH administration, for example fibronectin 1, alpha-HS-glycoprotein, and Vitamin D binding protein. 19,20 Another putative approach may be to longitudinally also monitor the different GH isoforms, since the isoform ratio appears to be quite stable in each participant. However, studies on the intra-subject variation of the isoforms using different kits are warranted to assess the value of including isoforms as ABP markers.…”
Section: Discussionmentioning
confidence: 99%
“…DBS sample extraction of actual whole blood or modeled‐blood samples spotted on filter paper was performed as previously described with minor modifications. One whole blood spot was punched out manually and the filter paper circle was transferred to clean tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, alternative matrices for blood collection such as dried blood spots (DBS) are being explored . In this sense, recent studies have demonstrated the feasibility of a single DBS to detect recombinant human growth hormone (rhGH) abuse by WADA required methods as well as the detection of new potential indirect biomarkers for such an rhGH abuse . Traditionally used for newborn screening of metabolic diseases, DBS consists of the deposition onto a specific filter paper of drop (s) of blood collected via finger or heel prick .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the retrospectivity of fibronectin 1 analyzed from DBS as a potential biomarker for detecting hGH misuse was found to be particularly long. In the context of a clinical trial with 10 male volunteers (0.026 mg hGH/kg/day for 3 days), Ferro et al determined fibronectin 1 from DBS by means of immunological methods up to 216 hours post‐administration . DBS (25 μL) were extracted, diluted and assayed, demonstrating a significant increase in fibronectin 1 concentrations from 24 hours to 216 hours, which would substantially expand the window of opportunity for doping controls if confounding factors affecting blood fibronectin 1 concentrations can be excluded in future studies.…”
Section: Peptide Hormones Growth Factors Related Substances and MImentioning
confidence: 99%